The safety of autologous and metabolically fit bone marrow mesenchymal stromal cells in medically refractory Crohn's disease – a phase 1 trial with three doses. Issue 5 (7th July 2016) - Dhere, T.; Copland, I.; Garcia, M.; Chiang, K. Y.; Chinnadurai, R.; Prasad, M.; Galipeau, J.; Kugathasan, S.
Summary: Background: Mesenchymal stromal cells ability to reset immune functionalities may be useful in Crohn's disease. Aim: To perform a first‐in‐human phase 1 safety clinical trial of metabolically fit autologous bone marrow‐derived mesenchymal stromal cells in 12 subjects with Crohn's disease utilising three doses. Methods: Autologous mesenchymal stromal cells were derived from marrow aspirate and propagated for 2–3 weeks with fibrinogen depleted human platelet lysate and subsequently administered to subjects without interval cryobanking. Twelve subjects received a single mesenchymal stromal cell intravenous infusion of 2, 5 or 10 million cells/kg BW( n = 4/group). Infused mesenchymal stromal cells were analysed for cell surface marker expression, IDO(indoleamine 2, 3‐dioxygenase) upregulation by IFN γ stimulation, and inhibition of third party peripheral blood mononuclear cell proliferation in vitro . The primary end point measured was safety and tolerability; clinical response was assessed as a secondary endpoint. Results: All patients tolerated the mesenchymal stromal cell infusion well and no dose limiting toxicity was seen. Seven patients had serious adverse events of which five were hospitalisations for Crohn's disease flare. Two of these serious adverse events were possibly related to the mesenchymal stromal cells infusion. Five subjects showed clinical response 2 weeks after the infusion. Mesenchymal stromal cell phenotype, cytokine responsiveness, and peripheral blood mononuclear cell proliferation blockade were not different among the patients. Conclusion: Single infusion of fresh autologous bone marrow mesenchymal stromal cells propagated ex vivo using human platelet lysate‐supplemented media was safe and feasible at intravenous doses of up to 10 million cells/kg BW in patients with Crohn's disease.